Active distribution network type identification method of high proportion new energy power system based on source-load matching - Qinlin, Shi (2023)
A large number of distributed new energy and flexible loads are connected to the distribution network, resulting in increasingly complex source load characteristics and supply and demand situations. The analysis of source load characteristics and accurate division of network types are the basis for the accurate planning of active distribution networks. Here, we report an active distribution network type identification method based on source-load matching. Firstly, the typical daily output scenarios of DG are extracted by clustering method, and the generalized load curve model is solved by the optimization algorithm to obtain the source load operation data; Secondly, calculate the source-load matching indicators (including matching performance, matching degree, and matching rate) according to the source load data of each region, and identify the distribution network type according to the range of the index values; Finally, several indicators are introduced to quantify the characteristics of different types of distribution networks. A case study of a power supply grid in Zhejiang Province is used to verify the practicability of the proposed method for active distribution network planning.